2161. Pilot Implementation of a Nationwide Automated Multidrug-Resistant Organism Tracking and Alert System in Veterans Affairs. (26th November 2018) - Pfeiffer, Christopher; Jones, Makoto; Klutts, J Stacey; Lee, Rachael A; Williams, Holly B; West, Katelyn A; Strymish, Judith M; Safdar, Nasia; Harris, Bryan D; Gelman, Michael A; Decker, Brooke K; Murray, Adrienne; et al.
Abstract: Background: Regional spread of multidrug-resistant organisms (MDROs), including carbapenem-resistant Enterobacteriaceae (CRE), can occur when carriers present unbeknownst to healthcare facilities and thereby delay appropriate infection control interventions. Herein, we describe pilot implementation of a novel national system that automatically alerts local facility staff to newly admitted patients with any history of CRE or methicillin-resistant Staphylococcus aureus (MRSA) in VA. Methods: From December 2016 to November 2017, we implemented the alert system in 10 VA medical centers. The system continually monitors the VA Corporate Data Warehouse for new facility admissions nationwide among patients with archived CRE and MRSA data. When such admissions occur, an alert is emailed to Infection Prevention personnel at the local facility. During implementation, we upgraded to a faster, more accurate report, "MDRO Tracker", that provided alerts within 4 hours of admission. We evaluated system utility in three ways: (1) assessing user data and feedback; (2) comparing a dataset identifying all unique patients harboring CRE and MRSA to the subset of patients whose most recent positive result was identified at a different VA facility; and (3) enrolling a convenience sample of CRE and MRSA patients to validate system accuracy and assess whether the new system or existing infrastructure identified the MDRO first. IRB approval was obtained at each site. Results: The number of users increased over time and are shown in Figure 1. User feedback data are shown in Figure 2; 71/256 (28%) responses indicated that alert data were new and/or timely. Of all CRE- and MRSA-positive patients identified during the study period, 11/101 (11%) and 214/2, 390 (9%), respectively, had positive MDRO results originating from a different VA facility. Of the 61 CRE and 1, 720 MRSA patients enrolled by research staff, 21% ( n = 13) of CRE and 7% ( n = 71) of MRSA cases were first identified by the automated system. Conclusion: This pilot implementation of a novel automated MDRO alert system shows feasibility and potential for substantial utility of such a system. Further refinement and expanded β-testing of the system is underway. Disclosures: M. A. Gelman, Cepheid: Speaker, Speaking Fee.